Non-invasive blood flow measurement using diffuse correlation spectroscopy - Melda. (2010)
Diffuse Correlation Spectroscopy (DCS) is an emerging method that measures blood flow in small vessels of deep tissue non-invasively. It uses the dynamic fluctuations of speckle pattern formed by photons that are scattered by blood cells. Possible DCS applications include stroke monitoring, breast cancer diagnosis, and brain functional imaging. The purpose of the author’s project was to build a single channel DCS device and validate its performance by doing several control experiments. Several control experiments with simulated particle motions and a subsequent in-vivo experiment with cuff occlusion were conducted. The results generated from the established DCS device were the inverse of theoretical expectation. However, qualitatively, the device was able to detect changes of blood flow. The reason of this discrepancy is discussed in the text. In addition, the author was able to develop real time DCS data acquisition and analysis program which can be used for continuous monitoring of relative blood flow over time. In summary, the DCS device which was built offers a promising possibility for continuous blood flow monitoring. Several improvements on the device were still required for obtaining better measurements. This project could eventually be combined with Diffuse Optical Tomography (DOT) which measures deep tissue hemodynamic variables non-invasively. This instrument can provide a non-invasive measurement of local metabolic rate thereby enabling more accurate functional imaging of human body.